Ahli Sunnah Perlis: Kelahiran dan Perkembangannya - @ Mahmood Daud, Zakaria (Jurnal Usuluddin, 1997)
The article tries to make a detail description of Ahl al-Sunnah wa al-Jama'ah of Perlis which is said to adhere only to the Quran, Sunnah Rasulullah and the opinion of the ulama of salafus-salleh and does not commit itself to any of the existing mazhab. It is also an attempt to trace its development from its early period to the present moment, its founders and the main supporters. The movement has made its attempt to spread its particular concept of Ahl al-Sunnah to other states in Malaysia.